Static output feedback design for unmanned aerial vehicle control - Комнацька, М. М.; Галагуз, Т. А.; Савченко, О. В. (Proceedings of National Aviation University (archive), 2013)
A contemporary approach for static output feedback design via linear matrix inequalities is proposed. The obtained solution guarantees stabilization of Unmanned Aerial Vehicle during flight envelope. During flight the unmanned aerial vehicle is subjected to the external disturbances. The efficiency of the proposed approach is demonstrated by a case study of Unmanned Aerial Vehicle longitudinal motion